“THE MECHANISM OF THE INFLUENCE OF THE NASOPHARYNGEAL MICROBIOTA IN THE DEVELOPMENT OF ANTIBIOTIC SUSCEPTIBILITY IN CHILDREN.” (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The use of antibiotics in children - in most cases - is confirmed by extrapolation of data obtained from clinical trials in adult populations. This puts children at higher risk of developing adverse drug reactions due to off-label drug use and dosage issues. The main types of adverse reactions are drug hypersensitivity reactions, an idiosyncratic type of adverse reaction that is largely unpredictable and can cause high morbidity and mortality in a difficult to identify specific patient population. The lack of complete understanding of the pathophysiology of DHRs and their unpredictable nature make them problematic in clinical practice and drug development.